(untitled) (Estudios Sociales, 2022)
Faced with the COVID-19 pandemic, the Argentine government developed two major policies to support households and businesses, the Emergency Family Income (IFE) and the Emergency Assistance to Labor and Production (ATP) program. This article analyzes their design and dilemmas of justice based on interviews with their political decision-makers. It shows that both measures were created at great speed, through a strongly centralized at the national level process, and with singular articulation between different ministries and state agencies. Although they were formulated by the same team, they were very different in their scope and their adjustments in response to problems unnoticed at the beginning. Therefore, the ATP can be classified as a policy of flexible design or "fine tuning" and the IFE as a policy of rigid design or "thick tuning". The reasons for this divergence are both technical and political.